Groundwater quality of shallow wells on Nigerian poultry farms - Aderemi, Peter Adeoye; Che Man, Hasfalina; Mohd Soom, Mohd Amin; Mohammed, Thamer Ahmad; Oluwakunmi, Akinbile Christopher (2014)
In the present study, an assessment of water quality from 20 randomly selected shallow wells inside poultry farms in Minna, north-central Nigeria, was carried out in order to establish the effects of a poultry waste dump located close to the wells by determining some physico-chemical and microbiological parameters of the groundwater samples. Samples of water were collected from the shallow wells between November 2011 and January 2013, and analyzed for physical, chemical, and bacteriological parameters. Sampling was carried out during the dry and wet seasons to find out if the water quality changes with the season. Analysis of variance was used to analyze the results and the means obtained were compared with the New Duncan Multiple Range Test. The results of the bacteriological parameters showed that the water quality is very poor; highly contaminated with faecal matter. Only 15% of the water samples satisfy the WHO guideline of 0 cfu/100 ml in dry season but reduced to 5% in the wet season. For total coliform, 10% satisfy the WHO guideline value in the dry season but none of the wells sampled was totally coliform-free in the wet season. About 25% were free from faecal streptococci during the dry season, but only 5% was free from these bacteria in the wet season. Statistics (p> 0.05) shows significant difference between coliform values in the wet and dry seasons. Generally the wells are polluted with coliforms, which may have migrated from poultry waste dumps into the wells. The difference in physical parameter values was also statistically (p>0.05) significant between seasons, with 55% of the water samples satisfying WHO 5NTU turbidity value in the dry season but the reducing to 30% in the wet season. Lower values were recorded for TDS and EC in the wet season than in the dry season. For chemical tests, 50% of the water met up with WHO 50 mg/L nitrate guideline in the dry season and were reduced to 35% in the wet season. Statistics (p>0.05) show no significant difference in the phosphate values for wet and dry seasons. It is clear from these results that water from the shallow wells is more contaminated in the wet season than the dry season.